ANALISIS KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENGEMBANGKAN KOMPETENSI GURU DI SEKOLAH DASAR NEGERI 270 LEBANI KECAMATAN BELOPA KABUPATEN LUWU - Nuryanti Nuryanti; Besse Herlina; Darmawan Darmawan; Mahira Mahira; Ramiati Solle; Hasmiani Hasmiani; Ardasir Ardasir (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of transformational leadership by the principal in developing teacher competencies at Public Elementary School 270 Lebani, Belopa District, Luwu Regency. The research was conducted using a descriptive qualitative approach, employing in-depth interviews, participatory observation, and documentation study. The findings reveal that the principal applies transformational leadership through four main dimensions: role modeling, inspirational motivation, intellectual stimulation, and individualized consideration. These dimensions directly contribute to the improvement of teachers’ pedagogical, professional, social, personal, and digital competencies. The novelty of this study lies in the integration of digital competence as part of teacher development within the context of the Merdeka Curriculum, as well as the reinforcement of the principal’s role as an agent of change in rural areas. The conclusion emphasizes that transformational leadership is key to creating a school culture that supports learning innovation and sustainable professional development of teachers.